PROLOTERAPIA UTILIZANDO GLICOSE HIPERTÔNICA NO TRATAMENTO DE DOR LOMBAR: ENSAIO CLÍNICO RANDOMIZADO - PIRES, José Alberto Pereira (2022)
Introduction: Chronic low back pain is pain that persists for more than three months and is one of the medical conditions with the most significant social impact, affecting 80% of adults. Objetive: To compare conservative therapy and prolotherapy with hypertonic glucose in chronic low back pain patients. Materials and methods: Cohort clinical trial, randomized, unblinded, with patients allocated into two groups, conservative therapy and 75% Hypertonic Glycemia, evaluated and followed up at the clinic "Oficina da Coluna" at the Macroregional Hospital, Pinheiro – MA. Results: Were included 19 patients in the Conservative group and 19 in the Glucose group, with a predominance of women (57.9%), aged between 47 and 59 years (39.5%), mixed-race (76.3%), married or in a stable relationship (73.7%), 5.2 years of study, mean BMI of 27.3±4.4 kg/m2, higher in the conservative group with 28.0±4.7 kg/m2, however, there was no significant difference (p-value = 0.938).. The groups showed differences concerning the Visual Analogue Scale, with median and amplitude close between the evaluated moments, increasing in the Glucose group, which, in the third evaluation, presented significantly higher values for this scale (p-value = 0.031). Comparing the groups on the Rolland-Morris scale, only in the 3m assessment was a significant difference, with a lower median observed in the conservative group (p-value = 0.021). Assessing the follow-up, both groups showed a significant improvement between T0 and the other evaluation moments, p- value < 0.05 in all evaluations. Conclusion: Both groups showed significant improvements during follow-up on the evaluated scales. Thus, prolotherapy was not more effective than the conservative approach. Overall, no effects were attributable to the glucose components and prolotherapy protocol.